1989
DOI: 10.1111/j.1600-0404.1989.tb03866.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of thymoma in Chinese myasthenia gravis: possible relationship with Epstein-Barr virus

Abstract: Thymectomy was carried out for treatment of myasthenia gravis in 27 unselected Chinese patients and thymoma was found in 13 of them. This 48% incidence of thymomas is two to three times greater than in Japanese and European patients, respectively. The reason for the higher incidence of thymomas observed in Chinese patients may be related to the presence of the Epstein-Barr virus genome in thymoma. Furthermore, all of the thymomas in our patients were lymphoepithelial and histologically resemble nasopharyngeal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Some research favors this hypothesis. It turns out that thymoma has a higher incidence in China where EBV is endemic [5]. This could be related to the increased presence of the Epstein-Barr virus genome in thymoma, as suggested in one study [6].…”
Section: Discussionmentioning
confidence: 96%
“…Some research favors this hypothesis. It turns out that thymoma has a higher incidence in China where EBV is endemic [5]. This could be related to the increased presence of the Epstein-Barr virus genome in thymoma, as suggested in one study [6].…”
Section: Discussionmentioning
confidence: 96%
“…Further study would be necessary to confirm this hypothesis; however, different associations of HLA and other T‐lymphocyte antigens have been demonstrated between thymomatous and non‐thymatous MG previously 31,32 . A role for EBV infection in the initiation of either specific tumour types or the autoimmune response in the Maori and Pacific Island populations also remains possible 17 . The investigation of thymoma tissue (with or without associated MG) in Maori and Pacific Island people for the presence of the EBV genome may also provide greater insights into the pathogenesis of this disorder.…”
Section: Discussionmentioning
confidence: 98%
“…Ethnic differences in the presentation of MG with thymoma have not been well described previously. Teoh et al have suggested that there is an increased incidence of thymoma among Hong Kong Chinese patients with MG compared with that described in other populations 17 . They have identified the Epstein–Barr virus (EBV) genome in two thymomas and have postulated an association with the increased rate of EBV‐related nasopharyngeal and salivary gland carcinoma in their population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Defective viral genomes have been isolated in patients with lymphoepithelioma-like thymic carcinoma. There is a reported association between Epstein-Barr virus (EBV) infection and tumors of the thymus.…”
Section: Etiology and Epidemiologymentioning
confidence: 99%